External Financing, Governance, and Infrastructure Development: Evidence From Sub-Saharan Africa - Noah, Afees Oluwashina; David, Oladipo Olalekan (CSID Journal of Infrastructure Development, 2024)
Infrastructure development in Sub-Saharan Africa (SSA) requires diversified financing strategies to address a significant funding shortfall that cannot be met by domestic resources alone. This research evaluates the contributions of external financing—namely Official Development Assistance (ODA), Foreign Direct Investment (FDI), and Private Participation in Infrastructure (PPI)—in complementing domestic efforts to advance infrastructure in SSA. It examines their influence, alongside governance, on the development of physical and social infrastructure components. Employing methodologies such as Panel-Corrected Standard Errors (PCSE) and System Generalized Method of Moments (SGMM) across 43 SSA economies from 2000 to 2022, the analysis reveals that FDI substantially enhances physical infrastructure development but does not significantly impact social infrastructure. In contrast, ODA is shown to have a negative direct effect on overall infrastructure development, whereas PPI shows no significant direct influence. However, when considering indirect effects mediated by governance, all external financing sources positively affect both types of infrastructure, except for PPI’s influence on social infrastructure. Theoretically, this study reinforces the critical roles of economic growth, institutional quality, and external financing in supporting infrastructure development, as suggested by related theories. The study recommends that SSA authorities should focus on attracting more foreign investment, particularly in physical infrastructure projects, and encourage a broader diversification of external financing sources beyond FDI alone. Moreover, enhancing governance practices is essential for effective resource allocation and utilization. The study also advocates for improved public spending efficiency through enhanced project prioritization and governance reforms to foster sustainable infrastructure development in the region.